Eﬀicacy of Decompressive Craniectomy in Managing Severe Stroke : A Systematic Review - Restiko Maleo Fibullah; Adistia Maulidiah; Hambali Humam Macan (The International Journal of Medical Science and Health Research, 2025)
Introduction: Severe stroke, particularly malignant middle cerebral artery infarction, is a neurological emergency with high mortality under conservative care. Decompressive craniectomy is a life-saving surgical intervention designed to mitigate high intracranial pressure. However, its efficacy is complex, with benefits in reducing mortality often challenged by poor functional outcomes and varying effectiveness across different stroke types. This systematic review aims to synthesize the current evidence on the efficacy of decompressive craniectomy in managing severe stroke. Methods: Following the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020 guidelines, a comprehensive search was conducted across PubMed, Springer, Semantic Scholar, and Google Scholar. The search used PICO-based keywords to identify randomized controlled trials, prospective studies, and meta-analyses published since 2015 that evaluated decompressive craniectomy in adults with severe ischemic or hemorrhagic stroke. Data regarding study design, patient characteristics, intervention timing, mortality, and functional outcomes were extracted from the 17 studies that met the inclusion criteria. Results: The evidence demonstrates that for severe ischemic stroke, early decompressive craniectomy (typically <48 hours) significantly reduces mortality, with rates dropping from approximately 70% in control groups to around 30% in surgical groups. Despite this survival benefit, a substantial proportion of survivors are left with moderate to severe functional disability (modified Rankin Scale score of 4). Conversely, in patients with supratentorial intracerebral hemorrhage, decompressive craniectomy was associated with worse functional outcomes and higher mortality compared to more conservative surgical interventions. Discussion: The findings underscore a critical clinical and ethical dilemma: the trade-off between survival and the quality of that survival. The decision to perform a decompressive craniectomy is complex and must be highly individualized, carefully considering the stroke etiology (ischemic versus hemorrhagic), patient age, and the timing of the intervention. Open communication with families regarding the high likelihood of survival with significant dependency is essential for shared decision-making. Conclusion: The evidence synthesized in this systematic review unequivocally establishes decompressive craniectomy as a life-saving intervention for patients with severe ischemic stroke, particularly malignant middle cerebral artery infarction. The procedure dramatically reduces mortality rates when compared to conservative medical management, a finding that is robust across numerous high-quality studies. This survival benefit is most pronounced when surgery is performed early, ideally within 48 hours of stroke onset, cementing its role as a critical and time-sensitive treatment in the neurocritical care setting for this specific patient population.